Risk Factors for Primary Dysmenorrhea in Students of Public Health Faculty, Nusa Cendana University - Aka Kale, Yislin Aplonia; Weraman, Pius; Tedju Hinga, Indriati A. (Timorese Journal of Public Health, 2022)
Dysmenorrhea is one of the disorders experienced by women that causes physical discomfort so that it causes disruption of daily activities including lectures and work as well as a decrease in productivity both in work and study . The Public Health Sciences Study Program, Faculty of Public Health, is one of the study programs with a large number of female students. Data on the highest number of female students in the IKM study program, namely in the class of 2018 with the number of students 362 people. The purpose of this study was to determine the relationship between the duration of menstruation, exercise habits, the habit of consuming junk food, stress in female students with a degree of primary dysmenorrhea. This type of research is an analytical survey. The design of this study is cross sectional. The population is a student of the class of 2018 IKM Undana Kupang. The sampling technique is a random sampling system with 186 respondents. The data was collected using a questionnaire in the form of a google form that was shared online. Statistical test using chi square technique. The results of the study showed a relationship between the duration of menstruation (p value = 0.000), the habit of consuming junk food (p value = 0.000), stress (p value = 0.000) with the degree of primary dysmenorrhea in students of the class of 2018 IKM Undana Kupang and the absence of a relationship between the ability to exercise (p value = 0.61) and the degree of primary dysmenorrhea in students of the class of 2018 IKM Undana Kupang. It is recommended to maintain a healthy and begizi consumption pattern, avoid things that cause stress, maintain a healthy lifestyle so that dysmenorrhea pain does not interfere with activities both academic and non-academic.